ENTERPRISE PROFIT AND IT IN THE CONDITIONS OF MODERNIZATION OF THE COUNTRY WAYS OF MAXIMIZATION - Abdug’aniyeva Zulkhumor Alijon qizi; Mamayusupova Dilovarkhan Begmatovna (Galaxy International Interdisciplinary Research Journal, 2024)
This article discusses the need to modernize, reorganize, enter the world market with quality and competitive products at the level of the country and the enterprise. It is written about the implementation of important changes in the field of technical technologies, education, and the quality of personnel in our country.